Improved deposition modelling for heat exchangers in pulverised fuel combustors - Riccio, Chiara (Cranfield University, 2019)
Co-firing biomass with coal is a promising and cost effective solution to reduce CO₂ emissions derived from the use of fossil fuels in existing power generation systems. However, deposition on heat exchangers (i.e. fouling and slagging) represents a major problem in power plants as it reduces boiler thermal efficiency, causes fireside corrosion and compromises the life of components until forced shutdown. The high complexity and multidisciplinary nature of this problem, which varies with boilers, fuel composition and combustion conditions, has made its prediction a major challange. In this thesis, Computational Fluid Dynamics (i.e. CFD) software, Ansys Fluent® , was used and its features were enhanced with three User Defined Functions (i.e. UDFs) which were modified to predict deposit accumulation, deposit shape and surface temperature. The Eulerian-Lagrangian model was enabled to describe the gas flow field around tubes and the solid ash particle trajectories respectively. Unsteady simulations were run and the combined effect of deposit growth and surface temperature on the deposition flux calculations was included. Experiments of co-firing Daw Mill coal-12 wt.% Miscanthus were carried out in a 100 kWth pilot-scale pulverised fuel (PF) combustor at Cranfield. The flue gas temperature and composition were recorded and fly ash samples were analysed to fit the Rosin Rammler ash particle size distribution model. Moreover, deposits were collected on cooled ceramic probes to measure the deposition flux and the chemical composition. The CFD model was applied to predict deposition on the cooled ceramic probes and the experimental results were used to set boundary conditions and to validate the model. The main challenges met in this work have been highlighted and possible solutions suggested. The model included several deposition mechanisms for ash particles and vapours and took into account the stickiness of the surface and the ash particles. Deposition has been studied for varying probe configurations and surface temperatures and the comparison between the experimental and modelling results was promising. Alkali vapour condensation enhanced the formation of deposit onto clean surfaces at lower temperatures. However, inertial impaction was the main deposition mechanism for bigger ash particles.
Oakley, John E. - Associate Supervisor
Keywords: Co-firing coal and biomass; fouling; particle deposition; vapour condensation; Computational Fluid Dynamics; unsteady simulations